Factors that attract customers to patronize bars and grilles - Arceo, Angelie T.; Arquisola, Ethel Marie L.; Mendoza, Jennifer J.; Monte, Michael Glenn G.; Tanlu, Therese Valerie P.
Kiosks have been sprouting inside shopping malls these days. Even outside the malls, we can see kiosks selling various products and services. This study has the kiosks in the five major shopping centers in Iloilo City as the study population. For the customers, the study population is composed of the residents in Iloilo City aged 12 years and above. This is conducted to determine how perceived factors such as location, competitors, customers, and products/services being offered, and marketing strategy affect the competitiveness of these kiosks. It would not be easy for these kiosks to profit since tenants and other kioskss pose as threat to income and customers have also different needs and wants. The most significant factors that affect competitivenesss of kiosks are related to how their management was able to induce buyers to purchase their products. The marketing strategy including advertising, granting of discounts and giving of orientation to their salespersons can attract customer thus, increase the competitiveness of kiosks. Moreover, it important that the management is able to relate the above-mentioned factors with customer's age, sex, occupation and income that affect the decision of what products to buy.